Les comités syndicaux jeunes: Acteurs du changement institutionnel ou voie de contournement? - Laroche, Mélanie; Dufour-Poirier, Mélanie (Labour / Le Travail, 2015)
Examines the participation of young workers in unions as well as their place in unions' committee structures. Considers the literature on integration of young workers into unions, the revitalization of unions through institutional change (three key criteria are delineated), and the results of a survey (interviews, focus groups) that was conducted by the authors. Concludes that youth should play a greater role than consultation and education — that they should have a voice rather than a presence in union councils — which in turn would encourage participation by other minority groups in union renewal.